Chrome waste as sorbent for the removal of arsenic(V) from aqueous solution - Low, K.S.; Lee, C.K. (Publications Division Selper, 1995)
The present study investigates the potential of chrome sludge, a waste material from electroplating industry, as a sorbent for the removal of As(V) from aqueous solution. Parameters studied include sorbent dosages, temperatures, different initial concentrations and pH values. The sorption of As(V) was rapid and the process of uptake follows the Langmuir isotherm model. Maximum sorption capacity of chrome sludge for As(V) was found to be 21 mg g-1.